Environmentally friendly carrageenan-based ionic-liquid driven soft actuators - Serra, João P. (2022)
UID/FIS/04650/2020 UID/QUI/0686/2020 LA/P/0008/2020 PID2019-106099RB-C43/AEI/10.13039/501100011033